A knowledge‐based human‐centred growth model for Latvia - Karnitis, Edvins (Journal of Business Economics and Management, 2006)
A growth model for Latvia is presented. The main resource for growth is the knowledge and wisdom of Latvia’s inhabitants, and the ability of each individual to make use of this resource. Raising the quality of life in every aspect for each individual is the main goal of growth. The collective knowledge of the people must be used to achieve this. In achieving this goal we must make use of coordinated and balanced development of each aspect of life, taking into account the unity of activities and the expansion these activities beyond frameworks of individual sectors, institutions, formal state structures and across borders. The model has been approved by Saeima (Parliament) in 2005. Several activities have been started to implement the model. Firstd Published Online: 14 Oct 2010